2020
DOI: 10.24018/ejfood.2020.2.5.126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cluster Bean (Cyamopsis Tetragonoloba (L.) Taub) Genotypes for Fruit and Gum Yield

Abstract: An experiment on evaluation of cluster bean genotypes was conducted at the department of vegetable crops, Horticultural College and Research Institute, Periyakulam. Fifty genotypes of gum type of cluster bean from NBPGR, Regional Station Jodhpur, two varieties viz., Thar Bhadavi and the check variety Pusa Navbahar were collected for the study. The collected fifty two (Ct - 1 to Ct - 52) genotypes were evaluated for their growth, yield and gum content for three seasons from November 2013 to February 2015. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
2
1
0
1
Order By: Relevance
“…Malaghan et al 2015, observed that variation in pods per cluster is caused at phenotypic and genotypic levels, there was a positive and highly significant correlation between the number of pods per cluster and the quantities of dry pods per plant, dry pod yield, seed yield, and clusters per plant. Comparable observation as recorded by Balakumbahan et al [9], number of pods per cluster was found to be in the range of 5.30 to 17.43 and number of pods per cluster for Pusa Navbahar was observed as 7.53, and Rai et al [7], in a study using 31 genotypes observed that pods per cluster was in the range of 5.40 to 14.10 and pods per cluster for Pusa Navbahar was observed as 7.97.…”
Section: Number Of Pods Per Clustersupporting
confidence: 86%
See 2 more Smart Citations
“…Malaghan et al 2015, observed that variation in pods per cluster is caused at phenotypic and genotypic levels, there was a positive and highly significant correlation between the number of pods per cluster and the quantities of dry pods per plant, dry pod yield, seed yield, and clusters per plant. Comparable observation as recorded by Balakumbahan et al [9], number of pods per cluster was found to be in the range of 5.30 to 17.43 and number of pods per cluster for Pusa Navbahar was observed as 7.53, and Rai et al [7], in a study using 31 genotypes observed that pods per cluster was in the range of 5.40 to 14.10 and pods per cluster for Pusa Navbahar was observed as 7.97.…”
Section: Number Of Pods Per Clustersupporting
confidence: 86%
“…Among the seven accessions studied, the accession CT CBE 002 recorded the maximum plant height of 156.34 cm followed by Pusa Navbahar (89.91 cm) and the minimum plant height was observed in CT CBE 003 (71.28 cm) and CT CBE 004 (74.70 cm). Variation in the plant height was also observed by Balakumbahan et al [9] during harvesting time, it was the highest in Ct -21 (199.00 cm) followed by Ct -14 (192.97 cm) among the selected genotypes under study, and concluded that Pusa Navbahar had the highest yield and the lowest plant height among the genotypes (101.80 cm). While Wankhade et al [10], in their study observed pod length to be in the range of 88.68 to 123.34.…”
Section: Plant Height (Cm)supporting
confidence: 72%
See 1 more Smart Citation
“…При испытании 50 образцов разного происхождения, данный сорт выделился по урожайности бобов и семян(Balakumbahan et al, 2020), при испытании 31 генотипа овощных образцов в штате Карнатака 'Pusa Sadabahar' также был среди наилучших образцов(Rai et al, 2012). В закрытом грунте образцы этого сорта из коллекции демонстрировали невыравненность по морфологическим признакам.Характеристики образцов овощного типа коллекции приведены в таблице 2.…”
unclassified